Pencegahan Kejahatan Deepfake: Studi Kasus terhadap Modus Penipuan Deepfake Prabowo Subianto dalam Tawaran Bantuan Uang - Yoan Shevila Kristiyenda; Jasmine Faradila; Christina Basanova (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Deepfake has become a serious threat in cybercrime, allowing perpetrators to deceive the public with highly realistic video and audio manipulation. This research aims to analyze the mode of cybercrime that utilizes deepfake technology, especially in cases of fraud involving manipulation of the faces of public figures. This study uses the literature study method by reviewing regulations related to cybersecurity, deepfake technology, and policies that have been implemented in various countries in dealing with this threat. The results indicate that the deepfake crime mode is growing by utilizing public trust in the faked figures. Despite the implementation of several regulations, early detection, law enforcement, and victim protection continue to face challenges. Therefore, stricter and more adaptive policies are needed, along with strengthening cooperation between the government and digital platforms and increasing public digital literacy, to reduce the risk of deepfake crime in the cyber domain.